Can female preference drive intraspecific diversity dynamics in brown trout (Salmo trutta, L.)?. Issue 3 (16th February 2015) - Gil, Jordi; Caudron, Arnaud; Labonne, Jacques
Abstract: Intraspecific diversity can be strongly impacted by the dynamics of reproductive isolation during secondary contacts. The high levels of hybridisation and introgression between Atlantic and Mediterranean lineages in contemporary populations of brown trout in the Northern part of the French Alps are a good case in point. After a long period of allopatry, which one assumes has facilitated their divergent phenotypic and genetic evolution, man has removed a geographical reproductive barrier via stocking the Atlantic lineage in the Mediterranean area, thereby potentially enabling gene flow between native and non native populations. We investigate how much a prezygotic reproductive behaviour, that is female preference for male phenotype, can influence hybridisation in natural environments, using subaquatic video recording of reproduction. Our statistical model indicates that female preference appears to be largely heterogamous: females tend to select dissimilar males with respect to their own phenotype; thus, rather than acting as a barrier to gene flow, female preference is favouring gene flow between lineages that have been artificially placed in sympatry. This finding based on observational data is in agreement with previously reported genetic data, high levels of hybridisation between the lineages. We suggest that a knowledge of reproductive behaviour in natural environments is an essential tool for biodiversity managers to assess the potential risks associated with the introduction into recipient populations of non‐native lineage fish at the intraspecific level.